2009
DOI: 10.1177/0272989x08322014
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Productivity Costs for Caregivers of Children with Spina Bifida: A Population-Based Analysis

Abstract: Background. Caregiver productivity costs are an important component of the overall cost of care for individuals with birth defects and developmental disabilities, yet few studies provide estimates for use in economic evaluations. Objective. This study estimates labor market productivity costs for caregivers of children and adolescents with spina bifida. Methods. Case families were recruited from a state birth defects registry in Arkansas. Primary caregivers of children with spina bifida (N = 98 ) reported thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…Prior research indicates that healthcare costs (and thus utilization) are consistently identified as the main cost driver of the overall burden, which mirrors findings in this study . A literature review of burden and cost‐of‐illness studies reported that the lifetime direct medical cost for those diagnosed with NTDs (including SB) is substantial, with the majority of costs being for inpatient care, treatment at initial diagnosis in childhood and comorbidities in adult life .…”
Section: Discussionsupporting
confidence: 78%
“…Prior research indicates that healthcare costs (and thus utilization) are consistently identified as the main cost driver of the overall burden, which mirrors findings in this study . A literature review of burden and cost‐of‐illness studies reported that the lifetime direct medical cost for those diagnosed with NTDs (including SB) is substantial, with the majority of costs being for inpatient care, treatment at initial diagnosis in childhood and comorbidities in adult life .…”
Section: Discussionsupporting
confidence: 78%
“…In a population-based 2001–2002 survey of Arkansas families with children and adolescents with spina bifida, 24.5% had upper-level lesions, which did not vary significantly by age. 28,34 Unpublished cross-sectional data from the National Spina Bifida Patient Registry 35 indicate that upper-level lesions are very common among adolescents and adults with spina bifida born prior to 1999 and less common among younger children (R Valdez on behalf of the CDC National Spina Bifida Patient Registry team, personal communication, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…28 That study estimated that each live-born spina bifida case had a discounted present value of avoided lost parental economic output that of approximately $159,000 in 2005 dollars, 28 which was adjusted to 2014 dollars (Table 1) and for increased child survival.…”
Section: Methodsmentioning
confidence: 99%
“…This differed from findings of a study of families of children and adolescents with spina bifida that both employment restrictions and other caregiving effects were highest when the child who was affected was younger than 6 years of age and diminished as the child matured (Grosse et al . 2009; Tilford et al . 2009).…”
Section: Discussionmentioning
confidence: 99%